PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI DESA PURWODADI WILAYAH KERJA PUSKESMAS MULIOREJO KAB DELI SERDANG TAHUN 2024 - Dina Indarsita; Sri Siswati; Wiwik Dwi Ariyanti; Juliandi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
The high maternal mortality rate in Indonesia is caused by several health and non-health factors, for example there are still many births assisted by traditional birth attendants or caused by disease or nutritional problems. The maternal mortality rate (MMR), which is an indicator of maternal health in Indonesia, is still high when compared with ASEAN countries. Knowledge about the danger signs in pregnancy helps reduce the Maternal Mortality Rate (MMR) by encouraging pregnant women to quickly seek health facilities. Early detection of danger signs allows prompt treatment, which can reduce maternal and infant morbidity and mortality. It is very important for pregnant women to know about the danger signs of pregnancy. If they encounter danger signs of pregnancy, they can immediately seek help from health workers. This research is descriptive in nature with the population being 40 pregnant women who live in Purwodadi Village, PKM Muliorejo Working Area, Deli Serdang Regency. Data was collected using a questionnaire, processed using a frequency distribution and presented in the form of narrative text. The research results showed that there were 5 pregnant women who had good knowledge about the danger signs of pregnancy (9.3%) and 14 people (14.4%) who had good knowledge about the danger signs of pregnancy and 15 pregnant women who had a positive attitude about the danger signs of pregnancy ( 37.5%) and 25 people (62.50%) had a negative attitude. Furthermore, it is hoped that the Health Service will intensify the education and counseling program regarding the danger signs of pregnancy in health service facilities and that pregnant women will be active in seeking information related to pregnancy health, especially regarding the Danger Signs of Pregnancy.